Role of EMT in drug resistance of breast cancer: molecular mechanisms and therapeutic strategies - Luo, Yifan; Sheng, Renwang; Tan, Xin; Gu, Jun (Frontiers in Oncology, 2025)
Breast cancer, as the most common cancer in women, is a highly heterogeneous and complex tumor. One of the important reasons for the poor prognosis and high mortality of breast cancer patients is drug resistance. More and more evidence shows that epithelial-to-mesenchymal transition (EMT) is a key driver of malignant behavior of breast cancer, and also the core promoter of drug resistance. Multiple EMT-related signaling pathways activate EMT-transcription factors (EMT-TFs) and interact with each other, ultimately inducing drug resistance. The role of EMT in promoting invasion and metastasis has been studied in detail and systematically summarized, but its role in drug resistance of breast cancer has not been elucidated comprehensively. The purpose of this review is to clarify the EMT-related regulatory network in breast cancer and the possible mechanisms of EMT-induced drug resistance. Moreover, we have discussed the potential therapeutic advantages of reversing EMT and drug resistance by effectively targeting key elements of the regulatory network, with particular emphasis on EMT-related signaling pathways and microRNAs. This review summarizes the drug resistance of breast cancer induced by EMT systematically, which is of great significance for solving the drug resistance problem of breast cancer and improving the prognosis of patients.